2014
DOI: 10.1016/j.cytogfr.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Death waits for no man – Does it wait for a virus? How enteroviruses induce and control cell death

Abstract: Enteroviruses (EVs) are the most common human viral pathogens. They cause a variety of pathologies, including myocarditis and meningoencephalopathies, and have been linked to the onset of type I diabetes. These pathologies result from the death of cells in the myocardium, central nervous system, and pancreas, respectively. Understanding the role of EVs in inducing cell death is crucial to understanding the etiologies of these diverse pathologies. EVs both induce and delay host cell death, and their exquisite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 117 publications
0
20
0
1
Order By: Relevance
“…CVB is known to extensively interact with and antagonize host cell pathways through various mechanisms, including via the activity of two virally-encoded proteases, 2A pro and 3C pro (Harris and Coyne, 2013, 2014). Although we found that RIP3 was involved in the facilitation of CVB replication in IECs by promoting autophagy, RIP3 is also a key component in the pro-inflammatory necrotic cell death pathway, which may be detrimental to CVB replication.…”
Section: Resultsmentioning
confidence: 99%
“…CVB is known to extensively interact with and antagonize host cell pathways through various mechanisms, including via the activity of two virally-encoded proteases, 2A pro and 3C pro (Harris and Coyne, 2013, 2014). Although we found that RIP3 was involved in the facilitation of CVB replication in IECs by promoting autophagy, RIP3 is also a key component in the pro-inflammatory necrotic cell death pathway, which may be detrimental to CVB replication.…”
Section: Resultsmentioning
confidence: 99%
“…However, factors including the virus strain and the infected cell type could contribute to the variability of CPEs. Previous studies have suggested that different enterovirus-specific proteins play regulatory roles in virus-induced CPEs (24). Host-specific factors that regulate apoptotic and cytokine/chemokine production pathways may also modulate CPEs and virus production independently (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…CVB also can antagonize the apoptotic pathway in cells, allowing viral replication to proceed for a longer amount of time necessary to maximize progeny (Harris & Coyne, 2014). For example, CVB can cleave cell components of the pro-apoptotic family, including TRIF (Mukherjee, Morosky et al, 2011), and viral 2B protein can act as viroporin disrupting Ca 2+ gradients necessary to initiate apoptosis (Campanella, de Jong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%